The Jurisprudential and Legal Characterization of Assisted Reproductive Technologies (A Comparative Study of Legitimacy and Regulatory Controls) - Sahib Hadhal, Assist. Lect. Saja (Basra studies journal, 2026)
This study examines the jurisprudential controls and legal regulations governing artificial fertilization techniques as a contemporary medical issue requiring both Islamic legal clarification and a legal framework capable of keeping pace with rapid scientific developments. The research problem stems from the urgent need to formulate a comprehensive legal theory within Arab statutory legislation inspired by the principles of Islamic Sharia in order to regulate the procedures associated with these techniques and address legislative gaps that may fail to encompass emerging developments. This necessitates a balance between medically justified permissibility and Sharia-based restrictions aimed at preserving lineage. The study adopts a comparative analytical approach and concludes that Arab legislation should be harmonized with the objectives of Islamic Sharia through the enactment of explicit legal provisions that ensure the highest standards of precaution and safeguard. It further recommends establishing clear legal frameworks governing liability arising from such procedures in order to protect the family structure and preserve lineage.